Effect of Family Background on Female Students’ Mathematics Performance - Karim, Aninganigu; Bornaa, Christopher Saaha; Abrokwah, Bernard Kissi-; Mohammed, Hafizdeen; Apoenchir, Henry Kwami; Karim, Sulemana; Owusu, Alexander; Susuoroka, Gabina; Kwakye, Dennis Offei (American Journal of Education and Practice, 2023)
Purpose: The study investigates the effect of family background on female students' mathematics performance in Ghana's Tamale Metropolis. Materials and Methods: The study was in line with the positivist assumption where a quantitative approach using descriptive design was used to collect the data. The sample was 488 respondents selected from form two (2) female senior high school students from the study area. The Pearson Product-Moment Correlation Coefficient, frequency, percentages, mean, and standard deviation was used to analyze the data. Findings: The study pointed out that family backgrounds (parental educational background, parents' financial status, gendered cultural norms, and parents' religious beliefs) influence female students' performance in mathematics. Implications to Theory, Practice and Policy: It was recommended that non-governmental organizations should include female students in financial empowerment programs such as CAMFED and others.